Brick and Mortar Dreams and Nightmares: a Historical Look at the Role of Home Ownership in Britain - Tihelková, Alice (American & British Studies Annual, 2021)
The nationwide preoccupation with the “property ladder” and the high premium placed on owning one’s own home have traditionally set Britain apart from other European countries, where renting has been a popular living choice carrying few negative social connotations. The view of home ownership as the affirmation of the individual’s full membership in society persists to this day, despite the UK currently facing a massive housing shortage and growing unaffordability of homes. Taking a historical perspective, the paper identifies the key developments that have contributed to home ownership acquiring such enormous social value for the British and reveals a number of adverse social consequences of the overemphasis on owner-occupancy. Special attention will be devoted to the concept of property-owning democracy and the Right to Buy policies spearheaded by Margaret Thatcher in the 1980s, with the aim of revealing how they contributed to the housing crisis Britain is experiencing at present. In addition to books dealing with history and cultural studies, the paper draws on recent sociological reports, blogs, newspaper articles and documentary films.